Design and implement a portable interface for data acquisition in wireless sensor networks - Yong, Dorance Hui Ru. (2012)
Development of Wireless Body Area Network (WBAN) has brought about benefits, especially to the health care industry. However, some challenges faced by the data acquisition in WBAN include requirements for reliable and efficient systems. Hence, this project aims to provide a reliable and efficient data collection management system for WBAN and also to design and develop a data collection testbed for channel characterization. This project mainly consists of 2 areas - design and implementation of reliable data collection management system and that of the user application.A testbed design was proposed to meet the project objectives and to eliminate some limitations faced by existing online performance analysis and offline channel modelling testbeds. Through implementation of applications written in nesC language in the TinyOS, the testbed is able to perform data logging, calculation of Received Signal Strength Indicator (RSSI) values, as well as delayed retrieval of data. User applications such as the Graphical User Interface (GUI) and writing data in files at the PC are implemented by programs written in Java language. The applications involved in this testbed include BaseStation1, PacketParrot1, RssiTest, OscilloscopeRssi, and Oscilloscope1. An experiment was carried out to validate the viability of the flash logging and RSSI calculation features of the PacketParrot1 against RssiDemo1. RssiDemo1 is a similar version of RssiDemo (an application provided by TinyOS) and it is modified by the author to suit the needs of the experiment.